2013
DOI: 10.1007/s00216-013-7469-x
|View full text |Cite
|
Sign up to set email alerts
|

Analytical techniques and bioactivity assays to compare the structure and function of filgrastim (granulocyte-colony stimulating factor) therapeutics from different manufacturers

Abstract: The FDA has approved more than 100 protein and peptide drugs with hundreds more in the pipeline (Lanthier et al. in Nat Rev Drug Discov 7(9):733-737, 2008). Many of these originator biologic products are now coming off patent and are being manufactured by alternate methods than the innovator as follow-on drugs. Because changes to the production method often lead to subtle differences (e.g., degradation products, different posttranslational modifications or impurities) in the therapeutic (Schiestl et al. in Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…While the main peak with an m/z value of approximately 18,800 represented the single charge of filgrastim, the m/z value of about 9,400 represented the double charge of filgrastim and the m/z value of about 37,700 could represent the single charge of the filgrastim dimer. e major peak had an average mass value in the range of 18,831-18,842 Da, which was in agreement with the molecular weight of the filgrastim standard reference (18,799 Da). is result suggested that the main component of these preparations is indeed filgrastim.…”
Section: Maldi-tof-ms Qualitative Analysis Maldi-tof-supporting
confidence: 81%
See 1 more Smart Citation
“…While the main peak with an m/z value of approximately 18,800 represented the single charge of filgrastim, the m/z value of about 9,400 represented the double charge of filgrastim and the m/z value of about 37,700 could represent the single charge of the filgrastim dimer. e major peak had an average mass value in the range of 18,831-18,842 Da, which was in agreement with the molecular weight of the filgrastim standard reference (18,799 Da). is result suggested that the main component of these preparations is indeed filgrastim.…”
Section: Maldi-tof-ms Qualitative Analysis Maldi-tof-supporting
confidence: 81%
“…Since the expiration of its patent, more than fifteen biosimilars are commercially available in the world. Although several comparability studies on their structures and function have already been reported in the literatures [16][17][18][19][20], this study is the first one, to the best of our knowledge, to compare all four drugs distributed in Italy based on the structural and functional point of view. is is important to properly inform end users (i.e., patients and medical staff) about biosimilar drugs as an alternative, rather than preventing them from using it due to lack of trust.…”
Section: Introductionmentioning
confidence: 99%
“…Another comparability exercise involving use of more than ten analytical methods on a laboratory purified GCSF has also showcased the effectiveness of such analytical platforms [18]. High performance liquid chromatography-mass spectrometry (HPLC-MS) followed by top down fragmentation (collision induced dissociation/electron transfer dissociation (CID/ETD)) and 2D heteronuclear single quantum coherence nuclear magnetic resonance spectroscopy (HSQC-NMR) have been exploited recently as orthogonal approaches for characterizing physicochemical properties such that comparability assessment could be carried out with greater conviction [19].…”
Section: Introductionmentioning
confidence: 99%
“…, the chemical shift depends on amino acid type, secondary and tertiary structure and the peak line-width is affected by quaternary and quinary structure and exchange kinetics between forms. Recently, several laboratories have applied 1D 1 H and 2D heteronuclear NMR profiling protocols for structure evaluation of protein therapeutics [10,13,14,24-29], including the proposed biosimilar rituximab at 22 mg/mL [15] and the NIST mAb at 40 mg/mL [12]. Previously Poppe et al [9] developed a 1D- 1 H diffusion filtering method, which reduced the sucrose peaks in the spectrum and was applied on Amgen’s proprietary mAb samples concentrated at 30 mg/mL in 9% sucrose or phosphate buffer [30].…”
Section: Introductionmentioning
confidence: 99%